Le secteur de la santé en Algérie entre arabisation, défrancisation et anglicisation - Fatima Zohra Chebab; Karim Ouaras (L’Année du Maghreb)
The language issue in Algeria continues to engage Algerian society, attracts the attention of many scholars, and astonish observers with its complexity and instability. It is an endless project, as in all Maghreb countries, evolving with constantly changing political contexts. After decades of ideological conflicts and projections which remained unfinished, this issue still constitutes a significant challenge in Algeria, driven by factors beyond linguistic ones. The "irrational" approach to this issue has led to social discomfort and tensions in various vital sectors in Algeria, including the healthcare sector. This sector serves as a space of linguistic encounter and conflict, revealing a complex linguistic cartography where French-speaking healthcare professionals, due to their training, coexist with an increasingly Arabized administrative staff, and patients with effective multilingual practices (Algerian Arabic, Berber, and French). In this space of care and advice, communication becomes increasingly difficult and prone to misunderstandings, uncertainties, and ambiguities.In line with the recent research dedicated to language practices in healthcare spaces, this article aims to examine the complexity of the linguistic cartography characterizing the hospital structure in the Algerian context. Based on sociolinguistic and discourse analysis approaches, this study focuses on the latest political-linguistic measures imposed on this sector and examines the instability of its linguistic praxis.Recent political upheavals in Algeria have placed the linguistic issue at the center of debates, escaping the multiple challenges faced both nationally and internationally. This situation has prompted a reevaluation of the status of national and foreign languages and a reconsideration of their primacy over one another.The predominantly French-speaking healthcare environment, which is inherently multilingual, is increasingly exposed to linguistic injunctive decisions: "Arabization, De-Francization, Anglicization." While, at first glance, the coexisting languages in Algerian hospitals seem to evolve somewhat harmoniously, the surrounding issues mark them with a conflictual dimension that can disrupt their effective functioning in addressing healthcare goals. This situation, revealing tensions and conflicts in the Algerian healthcare setting, is starting to worry healthcare professionals.Based on a qualitative and comprehensive approach, this study aims to examine the underlying issues of the new political orientation in terms of language planning advocating for the substitution of French with English in Algeria. This new direction is a result of diplomatic tensions between Algiers and Paris, primarily related to memorial issues. Failing to objectively resolve these tensions, the authorities have attempted to “de-francize” and anglicize after initially trying to Arabize. It does so by analyzing data from a qualitative survey conducted among healthcare professionals at the University hospital center of Mostaganem.The analysis reveals that the Arabization and subsequent attempts to Anglicize the healthcare sector are essentially efforts to "de-francize" an inherently French-speaking sector. Ignoring the expectations of healthcare professionals and Algerian society, these directive and coercive decisions may once again clash with the social dynamics, which are determined by complex logics.